SUBJECTIVE CRITERIA OF SELF-ACTIVITY CONTROL OF THE RUSSIAN AND SLOVENIAN MANAGERS: COMPARATIVE ANALYSIS OF PROFESSIONAL COMPETENCE - E. Boštjančič; F. S. Ismagilova; G. S. Miroljubova; N. Jansha (Russian State Vocational Pedagogical University, 2016)
Aim. The results of the first stage of the Russian-Slovenian crosscultural research are provided in the present article; the purpose is identification of the key factors that have an impact on the choice of control criteria of a management activity by the Russian and Slovenian leaders.Methods. Empirical information acquisition was made on the basis of the questionnaire «Subjective criteria of monitoring of activities performance» by G. Miroljubova and F. Ismagilova. The correlation analysis using nonparametric criteria (Kendall's tau-b and Spearman's rho), Mann - Whitney U-test and a method of descriptive statistics were used to process the received results of the research. Calculation of data was performed by means of a software package SPSS Statistics 17,0.Results. The research unit which is stated in the publication has comparative character and includes three stages. The difference of managers' positions in Russia and Slovenia concerning self-checking of managerial activities was studied at the first stage. When researching the Russian managerial activity, listeners and graduates of the Presidential program of preparation of a managerial personnel provided by the Business School of the Ural State Federal University named after B. N. Yeltsin (Ekaterinburg) were engaged. The research has showed that both groups of measurable and weakly-measurable parameters are equally presented in the structure of subjective control criteria among managers. The significant differences are revealed between average values of the measured criteria of all types (natural, binary, criteria of a ratio and fitting) in the Russian (56,11) and Slovenian (60,39) samples. Scientific novelty. Activities control is a capability of a person to influence on the process and result of own work that is an extremely important aspect of professional competence of leading experts and managers. This aspect should be considered in programs of managerial professional training; unfortunately, it is poorly considered when training the Russian managers. The research confirmed and expanded theoretical theses on national cultural differences in managerial processes of work evaluation efficiency.Practical significance. The proposed diagnostic model which has confirmed its practical consistency, and the questionnaire developed on its basis can be considered as working tools for monitoring of the content of activity and measurement of indicators of its control among managers of various organizations. The results of diagnostics can serve as the material for correction of educational programs for training of managers in higher educational institutions, and the academic content of further vocational training courses.